Pengaruh Sosial Media Pada Niat Pembelian Merek X yang Dimediasi oleh Ekuitas Merek - Natasha Dewi Azzarah; Rini Kuswati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of social media supervision, social media interaction, and social media information sharing on brand purchase intention of The Body Shop, with brand equity as a mediating variable. A quantitative approach was used with primary data collected through surveys distributed to 150 respondents who have purchased and are familiar with The Body Shop products. Data analysis was conducted using the Partial Least Square (PLS) method with the assistance of SmartPLS software. The results showed that social media supervision, social media interaction, and social media information sharing significantly and positively influence brand purchase intention and brand equity. Brand equity was found to mediate the relationship between the three independent variables and brand purchase intention. This study provides insights for companies to leverage social media as an effective marketing tool to enhance purchase intention and brand loyalty.